Rancang Bangun Sistem Informasi Inventory Peralatan Komputer Berbasis Website Pada PT Indonesia Toray Synthetics - Apriani, Desy; Aisyah, Euis Sitinur; Anggraini, Listya (Technomedia Journal, 2019)
PT Indonesia Toray Synthetic is a company engaged in the field of industry where technology is currently experiencing rapid progress and requires access to information systems that are fast, precise and accurate information to solve problems encountered as in the case of presentation of reports. As one of the leading textile companies abroad, PT Indonesia Toray Synthetic has a data input system that still uses different applications in each division or department. To input the data from the checking of computer equipment inventory in the Information System (IS) department at this time the computer equipment inventory system at PT Indonesia Toray Synthetic is still using a manual and slightly slow system where the checking of inventory is still recorded in the form and PIC or admin must come to the employee desk and computer equipment warehouse. Based on these problems, a website-based system was designed that would make it easier for PICs or admin to check computer equipment items without having to come to the employee's desk or to the inventory warehouse. PT Indonesia Toray Synthetic requires a computer-based system, especially in the manufacture of computer equipment inventory reports where the application for making computer equipment inventory reports is considered very important in the decision making process so that neatly arranged and stored data in a database are needed to be easily processed making inventory reports. This study aims to provide positive benefits in the work process of inputting computer equipment inventory and provide good and accurate results or reports on PT Indonesia Toray Synthetic. Keywords: Supplies, Computer Equipment, SWOT